2018
DOI: 10.18388/abp.2017_2313
|View full text |Cite
|
Sign up to set email alerts
|

Association of HindIII-polymorphism in kappa-casein gene with milk, fat and protein yield in holstein cattle*

Abstract: The aim of this paper was to evaluate the effect of genetic polymorphism of kappa-casein on milk production in Holstein cattle. Two hundred and ten Holstein cows were used in this study. We established genotype structure of cattle population and calculated allelic frequencies based on PCR-RFLP analyses. The three genotypes: AA (69.52%), AB (27.62%), and BB (2.86%) were detected. Frequency of allele A was 83.33%, and of allele B 16.67%. The Holstein cattle kept in Slovak Republic exhibit a high value of homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
1
5
0
9
Order By: Relevance
“…Comparative amino acid sequence analysis revealed that CN protein harbor higher amino acid variations in river buffalo (Mediterranean and Murrah) as compared to the swamp buffalo. The results of the present study are in line with previous studies (Masina et al, 2007;Azevedo et al, 2008;Massella et al, 2017;Rangel et al, 2017;Miluchova et al, 2018;Fan et al, 2020;de Oliveira et al, 2021) which reported the potential association of genetic variants in CSN genes with lactation performance, milk composition, and attributes of milk products. Thus, casein gene-based markers are important candidates for the selective breeding of buffalo to improve the quantity and quality of milk (de Oliveira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Comparative amino acid sequence analysis revealed that CN protein harbor higher amino acid variations in river buffalo (Mediterranean and Murrah) as compared to the swamp buffalo. The results of the present study are in line with previous studies (Masina et al, 2007;Azevedo et al, 2008;Massella et al, 2017;Rangel et al, 2017;Miluchova et al, 2018;Fan et al, 2020;de Oliveira et al, 2021) which reported the potential association of genetic variants in CSN genes with lactation performance, milk composition, and attributes of milk products. Thus, casein gene-based markers are important candidates for the selective breeding of buffalo to improve the quantity and quality of milk (de Oliveira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Однако большинство авторов по итогам своих исследований находият, что молоко от коров с превалированием аллеля В по гену CSN3 характеризуется высоким содержанием жира, белка, сухих веществ и лучшей сыропригодностью [12][13][14]18]. Следовательно, в рамках рациональной переработки целесообразно использовать молоко для производства сыров и продуктов молочнокислого брожения.…”
Section: Discussionunclassified
“…В качестве одного из таких маркеров рассматривается ген ϰ-казеина (CSN3), локализованный на 6-ой хромосоме генома Bos taurus [11,12]. Из 13 охарактеризованных вариантов гена ϰ-казеина крупного рогатого скота часто встречаемыми у большинства пород молочного направления являются аллели А и В CSN3, кодирующие соответствующие структурные элементы белков, различающиеся двумя аминокислотными заменами в 136 и 148 положениях полипептидной цепи [13,14].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Mohammadi et al (2013) reported that the observed heterozygotes of κ-CN gene were extremely lower than the expected one in Iranian Holstein cattle with H o value of (0.18) and H e value of (0.31). Additionally, Miluchová et al (2018) inferred that the Holstein cattle breed exhibit a high value of homozygosity with H o value of (0.2762) and H e value of (0.7222).…”
Section: Heterozygosity and Inbreeding Coefficient (F Is ) Of κ-Cn Genementioning
confidence: 99%